PENGARUH PEMANFAATAN KRIM GAMBIR TERHADAP PERAWATAN KULIT WAJAH NODA BEKAS JERAWAT - S, Ruth Friskila; Rahmiati, Rahmiati; Rosalina, Linda (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
Acne scars is on of skin disorder caused by the damage of the collagen which. Usually people who are vulnerable to acne often occurs between the ages of 18-25 years because at this age increased sebaceous glands due to hormonal changesGambir extract cream is one of the semi-traditional cosmetics that contain active substances catechins and Tannins act as antioxidants which can be used as a bleaching treatment of acne scars to restore tissue damaged collagen in the skin. This study aimed to analyze the effect of the use Gambir extract cream to the skin care facial acne scars assessment indicator.This study used a quasi-experimental methods with (Non Equivalent Control Group Design). The object of this study is acne scars and samplies taken through purposive sampling technique. Total sample are six people aged 18-25 years old with acne scars. Data collected from this study are primary data. Data analysis technique used is descriptive analysis and t test (independent samples t test).Based on the analysis of data, proving that skin care facial blemishes acne scars without using cream Extract Gambir in the control group (X0) did not change any results significantly until last treatment (8) while the acne scars treat with cream Extract Gambir in the experimental group (X1) showed no significant change from baseline (pretest) starting from after the second treatment and continued to progress until the last treatment (treatment to 8).Then homogeneity testing has been done it acquired two data have the same variance (homogeneous), therefore the value of t referenced in testing the hypothesis is t on Equal variances assumed. The above data shows that tcount is equal to (12.252), while the value t table for provisions df 4 at a significance level of 5% is equal to (2,776). Thus the price t count> t table (12.252),> 2,776) it is proved that the hypothesis does not differ significant influence on the use of cream extract Gambir in both groups of the facial skin care fade blemishes acne scars with a significant level of 5% is rejected , With b ahwa meaning there is the effect of using Gambir extract cream to fade acne scars. For that is expected to respondents and the public to always use cream Gambir extract in treating facial skin stained acne scars.Keywords: acne scars, Gambir, cream,ekstrak